Interrogating the transmission dynamics of Trypanosoma cruzi (Trypanosomatida, Trypanosomatidae) by Triatoma venosa (Hemiptera: Reduviidae) after the elimination of vector transmission by Rhodnius prolixus in Boyacá eastern Colombia - Medina, Manuel; Zuluaga, Sara; Martínez, María Fernanda; Bermúdez, Juan Carlos; Hernández, Carolina; Beltrán, Virgilio; Velásquez-Ortiz, Natalia; Muñoz, Marina; Ramírez, Juan David; Triana, Omar; Cantillo-Barraza, Omar (Frontiers in Cellular and Infection Microbiology, 2022)
Graphical Abstract